Users' perception of environmental functions provided by local government / Zaherawati Zakaria and Erny Arniza Ahmad - Zakaria, Zaherawati; Ahmad, Erny Arniza (Universiti Teknologi MARA, Kedah, 2009)
This research is about users' perception of environmental functions provided by local government focused on Kedah Local authorities. The primary objective of this study is to investigate the factors affecting the users' perception of environmental functions provided by local government in Kedah. Instead of that, the study also aims at examining the relationship between environmental functions and level of users' perception in Kedah, and finally to determine the most factors affecting the users' perception towards local government functions in Kedah local authorities. The sampling of this research is about 300 respondents in Kulim Municipal Council, Sungai Petani Municipal Council and Alar Star City Council. In this study, simple random sampling was used where only 100 respondents in each local authority were selected. This research used Pearson Correlation, Descriptive Statistic T-Test and ANOVAs for data analysis purposes. Data were collected from 228 users in October 2007 until January 2008. In this research five hypotheses were tested. The hypotheses which include cleanliness, collection and disposal wastes, drainage and sewage, sanitation and beautification programme was not rejected. Findings indicated that all independent variables have significance with user's perception of environmental functions provided by local government in Alar Star City Council, Sungai Petani Municipal Council and Kulim Municipal Council.